Pemberdayaan Masyarakat Melalui Pelatihan Digital Marketing Pada Industri Tenun Ikat Di Desa Troso Kabupaten Jepara - Ahlis Tsani,; Mintarsih Arbarini, (Joong-Ki : Jurnal Pengabdian Masyarakat, 2024)
Digital marketing is a basic skill that ikat weaving entrepreneurs must master to adapt to the digital era. This study aims to describe the strategies, processes, and factors that influence community empowerment through digital marketing training in the ikat weaving industry in Troso Village. This research uses a qualitative approach with descriptive methods. Data collection techniques were observation, interview, and document study. The results showed that the empowerment strategy was carried out through the situation and needs analysis stage, program planning and determination, program implementation and evaluation. The empowerment process is carried out through the awareness and behavior formation stage, the transformation of abilities and skills stage, and the enrichment stage. Digital marketing training is able to improve the abilities and skills of trainees in utilizing digital media more optimally seen from how digital marketing is applied to their business. Supporting factors that influence digital marketing training are the willingness and enthusiasm of trainees to develop, the rapid advancement of digital technology and the support of related parties. While the inhibiting factors are the individualistic character of the trainees and the lack of human resources empowered.